Primary sclerosing cholangitis in children with inflammatory bowel disease: An ESPGHAN position paper from the Hepatology Committee and the IBD Porto group - Rheenen, Patrick F.; Kolho, Kaija‐Leena; Russell, Richard K.; Aloi, Marina; Deganello, Annamaria; Hussey, Séamus; Junge, Norman; De Laffolie, Jan; Deneau, Mark R.; Fitzpatrick, Emer; Griffiths, Anne M.; Hojsak, Iva; et al. (Journal of pediatric gastroenterology and nutrition, 2025)
Objective We aimed to provide an evidence‐supported approach to diagnose, monitor, and treat children with inflammatory bowel disease (IBD) and primary sclerosing cholangitis (PSC). Methods The core group formulated seven PICO‐structured clinical questions. A systematic literature search from inception to December 2022 was conducted by a medical librarian using MEDLINE and EMBASE. Core messages from the literature were phrased as position statements and then circulated to a sounding board composed of international experts in pediatric gastroenterology and hepatology, histopathology, adult gastroenterology and hepatology, radiology, and surgery. Statements reaching at least 80% agreement were considered as final. The other statements were refined and then subjected to a second online vote or rejection. Results Regular screening for gamma‐glutamyltransferase (GGT) is essential for detecting possible biliary disease in children with IBD. MR cholangiopancreatography is the radiological modality of choice for establishing the diagnosis of PSC. Liver biopsy is relevant in the evaluation of small duct PSC or autoimmune hepatitis. Children who do not have known IBD at the time of PSC diagnosis should undergo initial screening with fecal calprotectin for asymptomatic colitis, and then at least once yearly thereafter. Children with a cholestatic liver enzyme profile can be considered for treatment with ursodeoxycholic acid and can continue if there is a meaningful reduction or normalization in GGT. Oral vancomycin may have a beneficial effect on GGT and intestinal inflammation, but judicious use is recommended due to the lack of long‐term studies. Children with PSC–IBD combined with convincing features of autoimmune hepatitis may benefit from corticosteroids and antimetabolites. Conclusions We present state‐of‐the‐art guidance on the diagnostic criteria, follow‐up strategies, and therapeutic strategies and point out research gaps in children and adolescents with PSC–IBD. What is Known • Primary sclerosing cholangitis (PSC) is an uncommon condition in childhood‐onset inflammatory bowel disease (IBD) with severe outcomes, and there is no consensus on diagnostic and treatment approaches. What is New • The European Society for Paediatric Gastroenterology, Hepatology and Nutrition Hepatology Committee and the Pediatric IBD Porto group formulated clinical questions considered to be relevant for the care of children with PSC‐IBD. • An evidence‐supported approach to diagnose, monitor, and treat children with PSC–IBD is presented here, as well as suggestions for future studies based on current knowledge gaps.